2020
DOI: 10.1101/2020.11.24.20237446
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

N95 respirators, disposable procedure masks and reusable cloth face coverings: total inward leakage and filtration efficiency of materials against aerosol

Abstract: Humans expel physiological particles continuously through normal respiratory activities such as breathing, talking, coughing and sneezing; a portion of these are aerosol in the size range <5.0 µm. Misconceptions exist on how to best implement face coverings as an effective preventive health measure against potentially infectious respiratory generated aerosol. The aim of this study was to characterise the performance of face coverings against aerosol when worn by individuals, and to quantify the maximum aero… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…73,82 Practical guidance on reducing leakage would therefore be required to pursue this strategy. For example, Duncan et al 82 found that surgical masks sealed via tie straps offered better face seal than ear loops.…”
Section: Discussionmentioning
confidence: 99%
“…73,82 Practical guidance on reducing leakage would therefore be required to pursue this strategy. For example, Duncan et al 82 found that surgical masks sealed via tie straps offered better face seal than ear loops.…”
Section: Discussionmentioning
confidence: 99%
“…Both Konda et al 12,13 and Duncan et al 14 have measured the filtration efficiency of woven fabrics, for particles up to five micrometers. Both groups find a large variability in filtration efficiency from one material to another, with filtration efficiencies in the range less than 10% to almost 100%, for particles with diameters of a few micrometers.…”
Section: Results For Particle Filtrationmentioning
confidence: 99%
“…Konda et al , 12,13 Duncan et al , 14 and Sankhyan et al 15 have all measured filtration efficiencies for a number of fabrics. They studied the filtration of particles in the size range we consider, which is 1 μ m. Zangmeister et al 16 studied the mechanism of filtration for smaller particles.…”
Section: Introductionmentioning
confidence: 99%
“…Both the fit factor and the protection factor refer to the total inward leakage (penetration through the filter and the leaks); however, the fit factor is a reserved term to quantify the performances of a mask during a standardized fit test. [54][55][56][57] of relying on volunteers instead of fitting masks on manikins are the qualitative illustration of the inter-and intrapersonal variability of the fitting, and the generation of a realistic exhalation flow which would be difficult to reproduce with a manikin. However, this technique does not provide information about the trajectories of the respiratory droplets.…”
Section: Me Thods De Veloped To Visualize the Le Ak Smentioning
confidence: 99%
“…Both the fit factor and the protection factor refer to the total inward leakage (penetration through the filter and the leaks); however, the fit factor is a reserved term to quantify the performances of a mask during a standardized fit test. 54 , 55 , 56 , 57 …”
Section: The Fit Factor As An Indicator Of the Protection Provided By...mentioning
confidence: 99%